Code-switching as a pedagogical strategy in classroom settings: the case of township schools in a South African Metropolitan Municipality - Marawu, Sithembele (Rhodes University, Faculty of Humanities, School of Languages, 2018)
The purpose of this study was to explore the use of code-switching as a pedagogical strategy in bi/multilingual classroom settings. It was prompted by the widespread use of codeswitching (CS) in classrooms, particularly in South African rural and township schools. This study highlighted that learners from disadvantaged backgrounds struggle to learn through the medium of English but aspire to acquire it because of its association with socio-economic advancement. However, poor proficiency in English excludes them from being part of the country's economy. Research studies show that there is a shift from the old orthodoxy which perceived CS as undesirable in classrooms to a new orthodoxy that acknowledges its academic contribution in classrooms. Although more research on classroom CS has been done, this study identified the need for development of new strategies on how to use CS effectively in classrooms as a linguistic and pedagogical resource. In line with critical classroom ethnography, qualitative interpretation of data was used to understand the teachers' discourse behaviour. Additionally, non-probability sampling - specifically purposive sampling - was used to collect data. These methods and approaches assisted in the analysis of the discourse of the three teachers who served as units of analysis in this study. These teachers relied on CS to impart the content of their subjects to the learners. It transpired from data analysis that teachers use CS in classrooms to achieve various functions like social and pedagogical functions. Another finding is that the switches teachers make do not affect the syntactic structure of the matrix language. Moreover, CS enhances understanding of the subject matter. This study concludes by stating that as learners are emergent bilinguals, additive bilingualism would be more ideal in the South African situation than subtractive bilingualism which parents and learners seem to prefer. Lastly, there is a need to harness CS as a communicative and pedagogical resource in classrooms.
Keywords: Code switching (Linguistics); Multilingual education -- South Africa; Education, Bilingual -- South Africa; Language and languages -- Study and teaching -- Bilingual method; English language -- Social aspects -- South Africa; Language and education -- South Africa; Language and education -- Social aspects -- South Africa